Evaluation of atrial electromechanical properties in patients with masked hypertension. (17th August 2020) - Özkan, Selçuk; Yılmaz, Ömer Çağlar; Yavuz, Bunyamin
ABSTRACT: Purpose: In this study, we evaluated the electromechanical properties of atriums in patients with masked hypertension by using tissue Doppler echocardiographic technique to predict the predisposition to atrial arrhythmias. Methods: A total of 118 subjects were included in the study. Twenty-four-hour blood pressure monitorization (ABPM) was used to determinate the masked hypertension in the study group. Tissue Doppler imaging was used to find intra-left and -right atrial electromechanical delay (AEMD) and inter-atrial electromechanical delay. The results compared between patients with masked hypertension and without. Results: There were 55 (%46.6) patients with masked hypertension and 63 (%53.4) patients without masked hypertension without any difference regarding age sex heart rate. No statistically significant difference was found in intra-right AEMD between the groups. Left ventricular end-diastolic and systolic diameters ( p <0.01 vs p=0.034), left ventricular posterior and septal wall thickness ( p < .01 vs p < .01), left ventricular mass index ( p <0.01), left atrium volume ( p = 0.02), and indexed left atrial volume ( p <0 .01) were high in patients with masked hypertension Inter-AEMD (48.07 ± 11.49 ms vs 43.73 ± 8.61 p=0.02) and intra-left AEMD (24.8 ± 6.35 ms vs 21.42 ± 7.99 ms p=0.013) were significantly higher in masked hypertensive patients. Conclusions: Masked hypertension shares the same clinical outcomes like overt hypertension. Any effort must be given to prevent unwanted events in masked hypertensive patients. According to our findings we suggesting that masked hypertensive patients must be evaluated for atrial arrhythmia.